Ujaran Kebencian pada Akun Instagram Willie Salim: Suatu Kajian Linguistik Forensik: Hate Speech on Willie Salim's Instagram Account: A Forensic Linguistic Study - Hayati, Nona Sintia Rizki; Sirulhaq, Ahmad; Mahsun, Mahsun (Information Technology and Science(ITScience), 2025)
This study aims to analyze hate speech on Willie Salim's Instagram account through a forensic linguistic approach. Hate speech on social media has become an increasingly complex social problem that affects many individuals and communities. Therefore, it is important to identify and analyze hate speech to support law enforcement in the digital realm. The research method used is descriptive qualitative. Data were collected through observation and documentation techniques on comments that were considered to contain elements of hatred, such as insults, threats, and other provocative speech, on Willie Salim's Instagram account uploads. This study also utilized lexical, semantic, and pragmatic analysis techniques to explore the language patterns in these comments. Based on the results of the analysis, several categories of hate speech were found, including: (1) insults, (2) blasphemy, and (3) spreading fake news. Each category was analyzed from a lexical, semantic, and pragmatic perspective, which showed certain language patterns used to express hatred. This study also revealed that hate speech is often conveyed in implicit and explicit forms to weaken or intimidate certain individuals. The implications of these findings indicate the importance of forensic linguistics in identifying hate speech as an initial step in the law enforcement process in the digital realm. In addition, this study is expected to contribute to the development of more effective regulations in dealing with hate speech on social media, thereby creating a safer digital space for its users.